Experimental study of tunnel effects on deformation mitigation in soft clay excavation using centrifuge and PIV - Yi Rui; Xin Zhang; Yanyi Xue; Zengle Ren (Scientific Reports)
Abstract In soft clay, deep excavations adjacent to tunnels cause complex soil–structure interactions. We conducted centrifuge tests with Particle Image Velocimetry (PIV) to simulate a staged deep-pit excavation near a model tunnel. A scaled retaining wall and tunnel lining were instrumented in a strongbox; the soil was consolidated and excavated in four stages under 60 g. PIV tracked soil and structure displacements while pore-pressure sensors recorded stresses. Tunnel position (beside vs. below the pit) and lining stiffness were varied to isolate their effects. The results reveal a shielding effect: the tunnel acts as a rigid strut that redistributes stresses and mitigates excavation-induced settlement. Surface settlement and retaining-wall deflection were lower than in a no-tunnel case. This shielding depends on tunnel stiffness and proximity: a stiffer tunnel provides greater soil restraint, whereas a flexible lining allows more movement. A tunnel close to the excavation (within roughly one to two pit depths) bears higher internal load but yields the largest reduction of far-field displacement. PIV shows soil arching: settlement above the tunnel is reduced, while heave develops at the pit base. Three characteristic uplift patterns emerge: a symmetric “hill”, a central “groove”, and an asymmetric “triangle” toward the tunnel. These patterns reflect how soil arching is altered by the adjacent tunnel and wall. We define a critical interaction depth where the tunnel’s role shifts from passive inclusion to an active structural element. When the tunnel lies in this vertical zone near the pit bottom, it markedly alters stress paths and uplift geometry. By highlighting the tunnel’s dual role—reducing wall deformation while sustaining higher internal stress—and by categorizing uplift shapes and the depth threshold of interaction, this study advances understanding of tunnel–excavation interaction. These contributions (quantified shielding metrics, uplift-pattern classification, and the critical-depth concept) provide a basis for design and deformation prediction in deep excavations near tunnels.